Continuum of Care in Speech-Language Pathology Student Placements: Identifying Key Learning Themes - Wardrop, Nicola; McAllister, Lindy; de Stefanis, Daniel; Martin, Felicity (International Journal of Practice-based Learning in Health and Social Care, 2017)
Despite growing evidence in favour of longitudinal integrated clerkships (LICs) for medical student placements, allied health student placements continue to address single caseload types, often representing one stage of the patient journey. This study explored perceptions of speech-language pathology (SLP) students in a continuum of care placement in Australia, following the patient journey of stroke survivors from acute admission to rehabilitation. Four pairs of students participated in 24-day continuum of care placements. Student clinical competence was assessed in the usual way using the COMPASS® tool to ascertain if students achieved required levels of competency and were not disadvantaged by the new placement structure. Student satisfaction was assessed with a 5-point Likert scale. Learning outcomes were explored in individual semi-structured interviews at conclusion of placement. Thematic analysis was undertaken on interview transcripts to identify key themes from interviews. All students achieved entry-level competency upon completion of their placement. Positive learning outcomes reported included improvement in understanding of the post-stroke journey, broadened clinical knowledge, improved adaptability to different clinical settings, and awareness of and ability to deliver patient-centred care. As a result of this placement model, students reported developing an increased sense of their professional role and responsibility in advocacy for the patient. It is recommended that continuum of care placements be considered as an alternative placement experience structure in hospital settings to enhance student learning of the patient journey.